17 Ocak 1995 Hyogo-Ken Nanbu (Kobe) depremi gözlem ve değerlendirme raporu = 17 January 1995 Hyogo-Ken Nanbu (Kobe) earthquake reconnaissance and assessment report - Aydınoğlu, M. Nuray. (İstanbul)
vi, 118 s.